Effect of copaiba oil in hepatic damage induced by acetaminophen in rats - Teixeira,Renan Kleber Costa (2013)
PURPOSE: To investigate the effects of copaiba oil on the hepatic damage induced by paracetamol. METHODS: Thirty six rats were distributed into six study groups (N=6): control group, that didn't receive the acetaminophen; Acetaminophen Group, that only received the acetaminophen; Prophylactic Copaiba Group 1, that received copaiba oil two hours before the acetaminophen; Prophylactic Copaiba Group 7, that received copaiba oil seven days, once by day, before the acetaminophen; Therapy Copaiba Group, that received the copaiba oil two hours afther the acetaminophen; and N-Acetyl-Cysteine Group, , that received the N-Acetyl-Cysteine two hours afther the acetaminophen. Euthanasia was performed after 24 hours. The serum levels of AST, ALT, alkaline phosphatase, GT, total bilirubin, direct bilirubin and indirect bilirubin and histological analisis were analized. RESULTS: The prophylactic copaiba group 7, therapy copaiba group and N-Acetyl-Cysteine Group showed amounts of AST and ALT similar to the control group; and the prophylactic copaiba group 1 showed similar levels to the acetaminophen group. There was no significant difference between the groups regarding the amount of alkaline phosphatase and GT (p>0.05). The therapy copaiba group showed the highest levels of bilirubin and was statistically different from the other groups (p<0.01) and this increased the costs of direct bilirubin. Regarding histopathology, the oil of copaiba administered prophylactic or therapeutic form for 7 days could decrease the amount of necrosis and inflammatory infiltrate. CONCLUSION: Copaiba oil administered prophylactically for seven days, and therapeutic could reduce liver damage caused by paracetamol similarly N-Acetyl-Cysteine, however, when treated with copaiba therapeutically showed increases in bilirubin, costs increasing fraction indirect.